Elimination of Indian Citrus Ringspot Virus in Kinnow by Using Phytoproteins with Shoot‐tip Grafting (Plant Tissue Culture and Biotechnology, 2017)
The combined beneficial effect of shoot‐tip grafting with phytotherapy of different phytoproteins obtained from roots of Boerhaavia diffusa and leaves of Clerodendrum aculeatum to eliminate Indian citrus ringspot virus (ICRSV) from Kinnow is reported. The study also reports the effect of these phytoproteins on the growth and proliferation of Kinnow explants when nodal segments from infected mother plants (confirmed by RT‐PCR) cultured in MS containing different concentrations of aqueous extracts of these individual phytoproteins. Shoot‐tips from these nodal sprouts were grafted on Citrus jambhiri under in vitro condition. Phytoproteins from C. aculeatum were found utmost effective in respect of elimination of 50% virus followed by B. diffusa (40%). In respect of promotion of growth and proliferation of nodal explants, B. diffusa was found most effective followed by C. aculeatum. The plants were considered virus‐free when they showed absence of ICRSV in both DAC‐ELISA and RT‐PCR tests.Plant Tissue Cult. & Biotech. 27(1): 1-11, 2017 (June)